Investigation of the effect of oxygen vacancies on the electronic properties of lizardite - Pecinatto, H.; Ghosh, Angsula; Mota, Cícero; Frota, C.A.; Gusmão, M.S.S.; Frota, H.O. (Applied clay science, 2023)
Doping and chemical substitutions of clay minerals have been very successful recently in the design of new novel materials. The serpentine mineral, lizardite has attracted a lot of attention due to its abundance in nature across the world and its eco-friendly behavior. A detailed study of lizardite has been performed to understand the effects of the presence of vacancies placed strategically at three positions of the structure, thereby leading to six different configurations. Formation energy calculations exhibit the possibility of obtaining all the conformations considered in this work. Moreover, free energy calculations demonstrate the stability at higher temperatures. The presence of the oxygen vacancies in the site that binds the Si atoms and also that between the Si atom and the Mg atom decreases the gap. However, the oxygen vacancy on top of the tetrahedral layer of the clay mineral induces an insulator-metal transition. Energy-bands and the density of states display the modified electronic properties of the system with vacancies. Lowdin-charge analysis and the isolines of the charge distribution in different planes provide information on the modifications brought about by the vacancies. Hence, vacancies have a vital role in controlling the band-gap. Moreover, the modifications of the other electronic properties could provide a promising route towards to achieving valuable thermoelectric materials. •Effect of oxygen vacancies in the electronic structure of lizardite.•Formation energy indicates the most probable structures due to vacancies•Insulating and metallic nature are observed depending on the position of the vacancy.•Charge transfer demonstrates the charge distribution of the atoms due to vacancies.